Reading the Shibboleth: Derrida - de Man - Rousseau - Esposito, Stefan (Revista de Letras, 2009)
This essay performs an original reading of Jacques Derrida’s “Acts,” a memorial written for Paul de Man that endeavors to answer the question, “What is the legacy of deconstruction?” with reference to the question of deconstruction as a type of community, and also with reference to the repercussions of deconstruction for our understanding of the limits of community (the problem of the shibboleth). Focusing on an interruption in “Acts” that concerns the “Rhetoric of Blindness” debate between Derrida and de Man over whether or not Rousseau should be read as a member of the community of deconstruction avant la lettre, the present essay argues against past evaluations of the debate that portray it in terms of simple antagonism. As Derrida makes clear in “Acts” the debate over whether or not Rousseau utters a certain type of shibboleth, and whether or not any text or speech act can off er a shibboleth concerning its self-conscious use of always already indeterminate language, aptly distills the problem of the limits of community and the conditions of possibility for community, a problem that must necessarily be thought through in any discussion of the legacy of deconstruction. Keywords: Deconstruction. Community. Shibboleth. Rousseau. Rhetoric.